Use of first bicarbonate after out-of-hospital cardiac arrest to predict mortality. (2nd May 2022) - Lopez-Sobrino, T; Izquierdo Ribas, M; Jimenez Trinidad, FR; Cepas Guillen, PL; Flores Umanzor, E J; De Diego Soler, O; Villela Dantas, A P; Eder Salazar, A; Camino Castrillo, L; Ayala Borges, B J; Moreno Monterde, E; Gillermo Galvez, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recovered out-of-hospital cardiac arrest (OHCA) is associated with high morbidity and mortality. Having prognostic tools within the first hours of admission to hospital is critical. The pH is a widespread arterial blood gas marker, but the influence of its respiratory/metabolic components has not yet been established. Purpose: The objective of the study is to analyze the utility of first bicarbonate measure as a predictor of in-hospital mortality after OHCA. Methods: This is a prospective observational study carried out on survivors to the initial phase of an OHCA, who were admitted to the Acute Cardiovascular Care Unit of our single terciary center. Clinical characteristics and initial blood gas data were analyzed. The primary objective was in-hospital mortality. Results: A total of 50 patients were included (2019-2021), of which 40% died during the course of the hospitalization. First pH determination showed significant differences between survivors and dead. Of its two components, the bicarbonate was lower in the patients who died (13.93 ± 3.01 vs. 18.48 ± 4.15, p <0.001) while the CO2 partial pressure (PCO2) did not show differences (53.89 ± 14.43 vs. 50.31 ± 13.07, p = 0.377). A ROC analysis was performed, and the bicarbonate had the best AUC as a mortality predictor (0.819, CI 95% 0.695-0.944, p<0.0001), compared to lactate (0.793, CI 95% 0.663-0.923, p=0.001) and pH (0.781, CI 95% 0.650-0.913, p=0.001). The best cut-off value for bicarbonate was 16.5 mmol / L (Log-rank < 0.0001), with a sensitivity of 84% and a specificity of 79% to predict survival. Conclusions: Bicarbonate was the best initial predictor of mortality after an OHCA, above pH, which, although being a good predictor, is potentially altered by PCO2 (which was not a good predictor).